Assessing Non-Revenue Water Reduction Strategies by Water Service Providers in Kenya (International Journal of Scientific Research and Management (IJSRM), 2023)
This study assessed the Non-Revenue Water reduction strategies used by Water Service Providers in Kenya. High NRW affects the financial sustainability of many WSPs in Kenya. The objectives of the study are to ascertain the NRW reduction strategies being used and establish the level of NRW reduction strategy implementation. The researcher used mixed methods approach in conducting this study. He also used stratified random sampling to select a sample of 61 companies from a target population of 81 active water companies in Kenya. The research design for this study was both descriptive and analytical in nature. A semi structured questionnaire was sent online to collect both qualitative and quantitative data from the respondents and analysed using SPSS. A reliability test was also done on the research instruments using factor method analysis. Four theories were reviewed during the study and the key ones being the Managerial Efficiency Theory and the Theory of Constraints. The findings of the study confirmed that all the NRW reduction strategies are being used by the water companies in Kenya. However, other strategies are widely used more than others. The findings also revealed that there are various factors that hamper the full implementation of NRW reduction strategies. The study recommends that management should allocate adequate resources and prioritize NRW reduction activities and fully implement NRW reduction strategies. Managers should also develop policies, procedures and build structures that help in implementation of NRW reduction interventions, leverage technology and ensure that the budget making process takes care of all NRW reduction strategies.